MBRS-57. TARGETING METABOLIC ADAPTATION IN MYC/MYCN AMPLIFIED PEDIATRIC MEDULLOBLASTOMA AND NEUROBLASTOMA. Issue 2 (22nd June 2018) - Delaidelli, Alberto; Negri, Gian Luca; Sidhu, Simran; Cran, Jordan; Remke, Marc; Pfister, Stefan; Kool, Marcel; Taylor, Michael; Maris, John; Leprivier, Gabriel; Sorensen, Poul
Abstract: BACKGROUND: The MYC oncogenes contribute to more than 50% of all human cancers, but their therapeutic targeting has proven challenging. MYC/MYCN amplification in childhood medulloblastoma (MB) and neuroblastoma (NB) determine aggressive disease and high mortality, underlying the need for novel and effective therapies. MYC-driven transformation is energy demanding and impairs cell survival under nutrient deprivation (ND), a characteristic stress condition within the tumor microenvironment. We recently identified eukaryotic Elongation Factor 2 Kinase (eEF2K) as a pivotal mediator of the adaptive response of tumor cells to ND. We therefore hypothesized that eEF2K facilitates the adaptation of MYC/MYCN amplified MB/NB to ND, and that inhibiting this pathway can impair tumor progression. RESULTS: Analyzing publicly available genomic databases and tissue microarrays, we found that high eEF2K expression and activity are strongly predictive of poor outcome in MB and NB (p<0.001), and correlate with MYC/MYCN amplification (p<0.001). Inhibition of eEF2K significantly decreases survival of MYC/MYCN amplified MB/NB cell lines in vitro under ND. Combination of eEF2K knockdown and caloric restriction determines a twofold growth decrease of MYCN amplified NB mouse xenografts. Finally, eEF2K inactivation significantly attenuated the ability of tumor cells to engage fatty acid oxidation under ND, suggesting a link between eEF2K, MYC transformation and lipid metabolism. CONCLUSIONS: eEF2K represents a critical mediator for the adaptive response of MYC/MYCN amplified tumors to acute metabolic stress, and is therefore a promising therapeutic target. Future studies will combine eEF2K pharmacological inhibition with caloric restriction mimetics, as eEF2K activity appears to be critical under ND.